The microbiota-derived bile acid taurodeoxycholic acid improves hepatic cholesterol levels in mice with cancer cachexia - Morgane M. Thibaut; Martin Roumain; Edwige Piron; Justine Gillard; Axelle Loriot; Audrey M. Neyrinck; Julie Rodriguez; Isabelle Massart; Jean-Paul Thissen; Joshua R. Huot; Fabrizio Pin; Andrea Bonetto; et al. (Gut Microbes)
Alterations in bile acid profile and pathways contribute to hepatic inflammation in cancer cachexia, a syndrome worsening the prognosis of cancer patients. As the gut microbiota impinges on host metabolism through bile acids, the current study aimed to explore the functional contribution of gut microbial dysbiosis to bile acid dysmetabolism and associated disorders in cancer cachexia. Using three mouse models of cancer cachexia (the C26, MC38 and HCT116 models), we evidenced a reduction in the hepatic levels of several secondary bile acids, mainly taurodeoxycholic (TDCA). This reduction in hepatic TDCA occurred before the appearance of cachexia. Longitudinal analysis of the gut microbiota pinpointed an ASV, identified as Xylanibacter rodentium, as a bacterium potentially involved in the reduced production of TDCA. Coherently, stable isotope-based experiments highlighted a robust decrease in the microbial 7α-dehydroxylation (7α-DH) activity with no changes in the bile salt hydrolase (BSH) activity in cachectic mice. This approach also highlighted a reduced microbial 7α-hydroxysteroid dehydrogenase (7α-HSDH) and 12α-hydroxysteroid dehydrogenase (12α-HSDH) activities in these mice. The contribution of the lower production of TDCA to cancer cachexia was explored in vitro and in vivo. In vitro, TDCA prevented myotube atrophy, whereas in vivo hepatic whole transcriptome analysis revealed that TDCA administration to cachectic mice improved the unfolded protein response and cholesterol homeostasis pathways. Coherently, TDCA administration reversed hepatic cholesterol accumulation in these mice. Altogether, this work highlights the contribution of the gut microbiota to bile acid dysmetabolism and the therapeutic interest of the secondary bile acid TDCA for hepatic cholesterol homeostasis in the context of cancer cachexia. Such discovery may prove instrumental in the understanding of other metabolic diseases characterized by microbial dysbiosis. More broadly, our work demonstrates the interest and relevance of microbial activity measurements using stable isotopes, an approach currently underused in the microbiome field.